The Effectiveness of Cognitive-Behavioral Group Therapy Anger and Assertiveness of Adolescents - Tavakoli, Mohammad Nima; Mirghaemi, Tahereh Sadat (International Journal of Education and Cognitive Sciences, 2022)
The present study was conducted with the aim of determining the effectiveness of cognitive-behavioral group therapy on adolescent anger and asertiveness. The present research was a semi-experimental type of pre-test, post-test and its design were in two groups (experimental group and control group) and two stages of pre-test and post-test with the control group. The statistical population included male adolescents of Karaj city in the age group of 12 to 18 years in 2022, among them 30 people who have high scores in the anger and aggression scale of Nislon et al. (2000) and low scores in the assertiveness questionnaire of Kotler and Giura and were willing to cooperate with the researcher, were selected and then randomly assigned to two groups of 15 people, experimental and control. The experimental group was subjected to cognitive-behavioral therapy group intervention, including anger management and assertiveness therapy by Patrick M. Reilly and Michael S. Shropshire during eight sessions, but the control group did not receive any intervention, then in both groups, anger and assertiveness questionnaires were repeated. Varzi was implemented (post-test). The collected data were entered into the statistical software for analysis.. After analyzing the data using covariance analysis test, the results showed: cognitive-behavioral group therapy is significantly effective in reducing anger and increasing assertiveness in male adolescents was (p